Communication in crisis. Changes to the paradigms of public communication - Amado Suárez, Adriana (2010)
Communication has been a key factor in the consolidation of modern institutions of and has accompanicd each of its transformations. But we are no longer modern, and therefore, the communication models that used to be so productive in the past century are now in crisis. Especially since a new communication model emerged changing the classic one-way direction of public communication and puning it under the spodight as never before. But it raises also a new ethical and social challenge that involves organizations raking citizens into consideration for once.